2022
DOI: 10.34310/jskp.v9i2.637
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Preceptor and Knowledge of Students on Triage Skills in The Emergency Unit

Abstract: Nurse profession students are required to have skills in triage. So that when students do triage, there will be no over-triage and under-triage. This study aimed to determine the relationship between the preceptor role and knowledge of nursing profession students' perceptions of triage skills. This study was a descriptive-analytic study using a cross-sectional approach. The sampling technique used a consecutive sampling technique where the research was conducted for one month. The number of respondents in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Research by Uema et al (2020) found that triage errors contributed to 14.9% (4 cases) of the total 27 cases of death in one of the hospitals in Surabaya City. Other data in Pekanbaru City and observations show that 5 out of 10 nurses in the emergency room make mistakes in triage, causing patients who need immediate treatment not to receive maximum care (Huriani et al, 2022;Xue et al, 2024). In the Gresik district, other research data showed that 5 out of 12 nurses in hospitals in September 2014 performed actions not in accordance with triage labeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Uema et al (2020) found that triage errors contributed to 14.9% (4 cases) of the total 27 cases of death in one of the hospitals in Surabaya City. Other data in Pekanbaru City and observations show that 5 out of 10 nurses in the emergency room make mistakes in triage, causing patients who need immediate treatment not to receive maximum care (Huriani et al, 2022;Xue et al, 2024). In the Gresik district, other research data showed that 5 out of 12 nurses in hospitals in September 2014 performed actions not in accordance with triage labeling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nursing students' knowledge of triage is also an important focus, as they will become holders of similar roles in the emergency room in the future. Research shows that students' knowledge about triage is still lacking, and there are still difficulties in identifying and understanding the parameters underlying the sorting of patients into appropriate categories (Huriani et al, 2022). In an effort to improve students' understanding and skills in the context of triage, the use of audiovisual learning media, such as animated videos, has been proposed as one of the effective approaches.…”
Section: Introductionmentioning
confidence: 99%